(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The issue addressed in this paper pertains to one of the most vulnerable humancategories – children with disabilities, and by implication, people withdisabilities. Many a time the behaviour “normal” people have toward the disabledin the community is faulty and degrading. Most often this is so because ofthe erroneous perceptions many of us have in regard with the worth such personshave. This paper advances the premise that disability is neither a degradingexperience nor should it affect how one’s dignity is being perceived. Disabilityis an unavoidable aspect of the human condition, a common experiencewe all share. Moreover, the biblical claim that we are created in God’s image,does not preclude disability, but rather it elevates the status of the disabled.